THE IMPORTANCE OF BADMINTON MEANS IN EDUCATING SPEED AND FORMS OF MANIFESTATION IN CHILDREN - Milon Alexandra Gabriela (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
Badminton is a sport where,for getting results psycho-motor skills are very . One of the most important is speed manifestations. All speed manifestations can be improve using exercises from other sports, but also with specific badminton means. While speed is a psycho-motor as we born with, it can be educated to a certain extent with exercise. It is very important that this capacity to develop from the stage of initiation in badminton. During a game of badminton, there are many changes of direction which has an important role and response speed and strokes occur during execution speed. Children velocity, although the manifestations may be educated with routes applied and movement games.